Processing Technologies of Lignocellulosic Biomass: Potentials and Constraints for Ruminant Feed Production - Simon Petrus Ginting (Indonesian Center for Animal Research and Development, 2021)
Lignocellulosic biomass (LCB) such as crop residues and agro-industrial wastes are renewable resources and available abundantly. It could play central role in sustainable feeding system of ruminant production. These materials are potential source of fiber to support optimum rumen function and energy supply. However, the LCB has important nutritional constraints that limit its utilization as feed for ruminants. This review is intended to discuss nutritional constraints of LCB as ruminant feed and the potentials and challenges of processes in upgrading the nutritional quality of LCB. The main polymer compounds in LCB are cellulose (30 to 60% ), hemicellulose (20 to 40 %) and lignin (15-25%) and its inter linkages make the energy contained in the LCB is less extractable by the ruminant digestive system. Physical, chemical and biological processing technologies have been well known as alternative means to upgrade the nutritive values of LCB. Recently, novel processing technologies of LCB such as ionic liquid, organosolv, sonication, and new screened rot white fungi (Ceriporiopsis subvermispora) and some older technologies using alkaline and acids have been studied and developed particularly for the purpose of biofuel production in the bio refinery industry. Processing technologies have different properties in degrading the lignin, degrading and solubilizing the cellulose and hemicellulose that all relate to the nutritive quality of LCB. Advantages of processed LCB in ruminant animals were indicated by increase in diet digestibility, intake, rumen fermentation and gain. It is concluded that numerous processing technologies are available to upgrade the nutritional quality of LCB, but there are obstacles to use some of these techniques for wide application in ruminant production system.